2019
DOI: 10.1158/1078-0432.ccr-19-0498
|View full text |Cite
|
Sign up to set email alerts
|

BRN4 Is a Novel Driver of Neuroendocrine Differentiation in Castration-Resistant Prostate Cancer and Is Selectively Released in Extracellular Vesicles with BRN2

Abstract: Purpose: Neuroendocrine prostate cancer (NEPC), an aggressive variant of castration-resistant prostate cancer (CRPC), often emerges after androgen receptor-targeted therapies such as enzalutamide or de novo, via trans-differentiation process of neuroendocrine differentiation. The mechanistic basis of neuroendocrine differentiation is poorly understood, contributing to lack of effective predictive biomarkers and late disease recognition. The purpose of this study was to examine the role of novel proneural Pit-O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 51 publications
3
60
1
Order By: Relevance
“…The upregulation of Ī±VĪ²3 in the donor cells (C4-2B in this study) may alter the cargo composition of the sEVs released by the cells and enable them to induce NED in the recipient cells. Previous examples of modulation of sEV cargo by a drug or a single molecule have been reported [ 35 ā€“ 37 ]. A recent publication [ 35 ] has also shown that enzalutamide treatment of LNCaP cells stably expressing AR induce changes in the sEV composition by increasing the levels of BRN2 and BRN4 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of Ī±VĪ²3 in the donor cells (C4-2B in this study) may alter the cargo composition of the sEVs released by the cells and enable them to induce NED in the recipient cells. Previous examples of modulation of sEV cargo by a drug or a single molecule have been reported [ 35 ā€“ 37 ]. A recent publication [ 35 ] has also shown that enzalutamide treatment of LNCaP cells stably expressing AR induce changes in the sEV composition by increasing the levels of BRN2 and BRN4 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…546,547 In addition, a model of MUC1-driven lineage plasticity in PCa shows that MUC1 can upregulate the expression of BRN2 by recruitment of MYC and subsequent binding to the promoter region of BRN2, which further contributes to SOX2 expression. 548,549 This series of molecular regulations indicates that MUC1 may act as an upstream effector to regulate SOX2-induced lineage plasticity of neuroendocrine trans-differentiation in PCa. 548 Finally, by integrating systemic analyses of GEMM with patient clinical data, Zou et al 550 provided conclusive genetic evidence that drug-induced neuroendocrine trans-differentiation of PCSCs is one of the main reasons behind treatment failure.…”
Section: Transition Between Non-csc and Csc States Definition And Chamentioning
confidence: 99%
“…551 Taken together, findings from different approaches, including clinical data, together with multiple in vitro and in vivo experimental models, strongly demonstrate that tumor cell plasticity-induced lineage switching enables PCa to escape from ARPI treatment. [543][544][545][548][549][550][551] Neuroendocrine trans-differentiation from NSCLC to SCLC. Similar observations of neuroendocrine trans-differentiation have been made for lung cancer, in which the transition from EGFR-mutant NSCLC to small cell lung cancer (SCLC) (Fig.…”
Section: Transition Between Non-csc and Csc States Definition And Chamentioning
confidence: 99%
“…Notably, SOX2 is part of the 'reprogramming cocktail' of four pioneer transcription factors that together are capable of converting differentiated fibroblasts into induced pluripotent stem cells (Takahashi & Yamanaka 2016). More recently, another POU-domain transcription factor, BRN4, was found to interact with BRN2 and enhance its regulation of SOX2 (Bhagirath et al 2019). Importantly, BRN2 is directly repressed by AR, an example of the extensive, direct interplay that occurs between the key factors controlling cell identity in prostate cancer (Fig.…”
Section: Interplay Between Transcription Factors and The Epigenome Inmentioning
confidence: 99%